ANALISIS PERAMALAN PENJUALAN DAN KEUNTUNGAN SAYURAN BUNCIS (Studi Kasus Di Pt. Tiga Bintang Sukses Jatiasih Bekasi Jawa Barat) - Adinda Pinoer Suci Prameswari; Muharam Muharam; Suhaeni Suhaeni (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
PT. Tiga Bintang Sukses (PT. TBS) as the holder of the Goedang Mayoer trademark is a company that strives in the field of providing the best fresh vegetables and fruits, by promoting the concept of farm to table or from farmers directly to consumers. One of the vegetables sold is chickpeas. Beans are one of the highest selling vegetables in the company but fluctuate due to uncertain demand from consumers, especially hotels, restaurants, cafes, and offices. In meeting consumer demand, the company cooperates with farmers. The purpose of this study is to find the best forecasting technique for vegetable sales in the company, to make a sales forecast level and to make an average profit from the sales forecast for the next six months for green beans at PT. Three Stars of Success. This study uses a quantitative approach. The method used in this research is a descriptive analysis and case study. Data collection techniques used using primary data and secondary data. Primary data is related to the company and uses a questionnaire. Secondary data comes from the company's internal data, namely sales of green beans from September 2021 to February 2022. The best forecasting technique for green beans is the multiplicative decomposition technique. The results of the level of sales forecasting show that the highest level of sales for green beans is 500.61 kg. The profit forecast for the next 6 months, has an average profit for green beans, which is Rp. 1,596,232.